Pengalaman Informasi Pengguna Media Sosial X Sebagai Sumber Informasi Hidup Sehat: Studi Pemanfaatan Autobase @diethingy - Aulia Rizky Puspitasari; Prasetyawan, Yanuar Yoga (Pustabiblia: Journal of Library and Information Science, 2025)
Human interaction with information is no longer limited to physical space, but has also penetrated into cyberspace. Along with the development of digital technology, cyberspace has become the main space for individuals to find, share and interpret information quickly and participatively, especially through social media. This study aims to understand the information experience of autobase X @diethingy users as a source of healthy living information. This research uses a qualitative method with a phenomenological approach. The data collection method was carried out by interviewing twelve active users of autobase @diethingy. The results showed that users utilize @diethingy autobase to share information, discuss, and also share support. This encourages active participation of users in accessing, understanding, and internalizing healthy living information in their daily lives. There are two sides of the experience experienced by informants when interacting with information in assessing the quality of information, namely the positive side and the negative side. The positive side shows that the available information is easy to obtain and apply in daily life. Meanwhile, the negative side felt by informants is that many new users spread misinformation, disinformation and hoaxes about healthy living, which is exacerbated by the silence and absence of health experts who usually share more valid and reliable information.